2001
DOI: 10.4049/jimmunol.167.3.1198
|View full text |Cite
|
Sign up to set email alerts
|

CD44 Is the Physiological Trigger of Fas Up-Regulation on Rheumatoid Synovial Cells

Abstract: CD44 is a ubiquitous molecule known as a hyaluronan receptor. However, the relevance of CD44 to inflammatory processes, for example, rheumatoid synovitis, remains unclear. In this study, we propose a novel function for CD44 using synovial cells from rheumatoid arthritis (RA) patients and demonstrated that CD44 cross-linking augmented Fas expression and subsequent Fas-mediated apoptosis of the cells: 1) cross-linking of CD44 on RA synovial cells markedly augmented Fas expression and its mRNA transcription; 2) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 37 publications
2
45
0
Order By: Relevance
“…Osteopontin is a molecule associated with cell adhesion and migration and functions through binding to CD44 and relates to the progression of atherosclerosis [11]. We have reported that stimulation of CD44 with mAbs or hyaluronan transmits the signal into the cells, which leads activation of T cells and cytokine or chemokine of release from monocyte/macrophage, synoviocytes and cancer cells [12][13][14][15]. While these hyaluronan-cell interactions in atherosclerosis were reported by some investigators [16][17][18][19], the functional relevance of CD44 on monocytes/macrophages to hyaluronan and ox-LDL has yet to be investigated.…”
mentioning
confidence: 99%
“…Osteopontin is a molecule associated with cell adhesion and migration and functions through binding to CD44 and relates to the progression of atherosclerosis [11]. We have reported that stimulation of CD44 with mAbs or hyaluronan transmits the signal into the cells, which leads activation of T cells and cytokine or chemokine of release from monocyte/macrophage, synoviocytes and cancer cells [12][13][14][15]. While these hyaluronan-cell interactions in atherosclerosis were reported by some investigators [16][17][18][19], the functional relevance of CD44 on monocytes/macrophages to hyaluronan and ox-LDL has yet to be investigated.…”
mentioning
confidence: 99%
“…Tight interactions with Fas might reasonably be expected to prevent the interaction with ezrin. This may provide one explanation for the controversial literature surrounding CD44, which has been described as both a pro-apoptotic molecule [40][41][42], and an anti-apoptotic and pro-metastatic protein [43][44][45][46][47]. The present study together with our previous data [26] provide one explanation for this controversy.…”
Section: Cd44 Regulates Apoptosismentioning
confidence: 47%
“…Interaction of sialidase with another virulence factor(s) seems necessary to cause the pro-apoptotic effects of M. alligatoris infection. A prominent candidate that emerged from our M. alligatoris genome survey is hyaluronidase (Brown et al, 2004), because in other diseases the host cell HA receptor CD44 is modulated by the specific combination of sialidase and hyaluronidase to transduce signals leading to inflammation, CD95 upregulation, and excessive cell death (Bartolazzi et al, 1996;Fujii et al, 2001;Gee et al, 2004;Hauptschein et al, 2005;Katoh et al, 1995;Lesley et al, 1997;Pure and Cuff, 2001). Although there is no consensus on the molecular mechanisms by which CD44 is linked to apoptosis (Hauptschein et al, 2005), HA fragments generated from the ECM by hyaluronidases stimulate HER2 and c-Src tyrosine kinase phosphorylation of cytoskeletal proteins, and Rho GTPase signaling, through desialylated CD44 receptor-specific networks (Ponta et al, 2003;Turley et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Sialidase can unmask the CD44 molecules which are present on the surface of most host cells, but prohibited from binding HA by sialylation (Bartolazzi et al, 1996;Gee et al, 2004;Katoh et al, 1995). Following CD44 desialylation, binding of low molecular weight HA fragments from ECM degraded by hyaluronidase (Gee et al, 2004;Lesley et al, 1997) initiates intracellular signaling by CD44 through networks leading to production of pro-inflammatory cytokines (Sague et al, 2004), synthesis of cytotoxic nitric oxide (Iacob and Knudson, 2005), and inappropriate apoptosis involving the "fibroblast-associated" (Fas) receptor CD95-mediated signal transduction pathway (Fujii et al, 2001;Menaker and Jones, 2003). Those observations formed our hypothesis that synergy of bacterial sialidase and hyaluronidase co-localized directly at the host-pathogen interface during infection might potentiate CD44-transduced signals leading to inflammation and host cell death in some niches, consistent with the fulminant necrotizing disease caused by M. alligatoris.…”
Section: Introductionmentioning
confidence: 99%